The Role of the Chinese Diaspora in China's Foreign Policy - Darmawan, Arif; Martin Darmawan, Soni (KnE Social Sciences, 2023)
This paper examines the People’s Republic of China’s diaspora as a tool of foreign policy from its founding (Mao’s era) to the present ( Jinping’s era). China’s diaspora policy evolved from time to time, showing the changing migration pattern and reflecting favorable global conditions. Chinese diaspora has become an instrument of China’s domestic policy and foreign policy agenda since Kuomintang to the Communist government era. One of China’s domestic agenda is the need to attract foreign investment –primarily through diaspora community. In the foreign policy field, there has been a significant continuity in its foreign policy objectives related to its diaspora policy. To strengthen its global ambition, China implemented “new diplomacy,” aiming to change how its neighbors view their ambition with the help of their diaspora communities. Thus, the estimated 50 million Chinese diasporas have become important assets in connecting China to the world. Keywords: Chinese Diaspora, new diplomacy, foreign policy